2005
DOI: 10.1539/joh.47.78
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Change after One Year from a Health Examination and its Relation to Attitudes toward Lifestyle Change in Japanese Male Workers

Abstract: In Japan, members of the workforce undergo a general health examination (GHE) in accordance with the Occupational Safety and Health (OSH) law and related regulations. Because of a marked increase in the number of workers with health risk factors related to lifestyle, the focus of the GHE is gradually shifting to prevention of lifestyle-related diseases 1) . Under the 1996 amendments to the OSH law and regulations, an employer is required to obtain a physician's opinion regarding the GHE results, act to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Any issues with the sample size aside, there was not enough of a time span from the baseline to follow-up measurements. An observational study, grouping subjects based on their intention to lose weight or not showed an increase in BMI over one year [26]. Statistically significant reductions in BMI have been observed in a period of just two months, but when the intervention being studied specifically focused on weight loss [27].…”
Section: Secondary Variablesmentioning
confidence: 99%
“…Any issues with the sample size aside, there was not enough of a time span from the baseline to follow-up measurements. An observational study, grouping subjects based on their intention to lose weight or not showed an increase in BMI over one year [26]. Statistically significant reductions in BMI have been observed in a period of just two months, but when the intervention being studied specifically focused on weight loss [27].…”
Section: Secondary Variablesmentioning
confidence: 99%